Effect of BN nanodomains on the mechanical properties of graphene monolayers. (March 2019) - Azevedo, S.; Kaschny, J.R.
Abstract: In the present contribution first-principles calculation was applied to investigate the modifications on the mechanical and electronic properties of a graphene monolayer induced by the inclusion of a boron nitride nanodomain. The calculation results indicate a significant reduction in Young's modulus. Such nanodomain can be seen as an extended defect, which can be pointed out as the crack seed for the layer disruption. The strain energy shows a quadratic behavior, which is typical for structures submitted to tensile strain. A significant increment in the band gap energy was found. Highlights: Young's modulus are significantly small than the ones obtained for graphene and BN. The BN nanodomain can be indicated as the crack seed for the material disruption. Significant increments in the band gap energy, up to 0.5 eV, were found.